The prevention of curcumin against rat liver mitochondrial swelling induced by tert-butylhydroperoxide (Medical Journal of Indonesia, 2006)
Liver diseases have been a medical problem which is difficult to manage. Some of the problems in the treatment of these diseases lie in the lack of reliable drug available. Curcumin, an active ingredient of the rhizomes of plant Curcuma has been investigated in the treatment of various disorders incuding liver diseases. The therapeutic effects of curcumin on liver diseases have been thought to be associated to its antioxidative properties. In the present study, we investigated the effects of curcumin on mitochondrial swelling in vitro induced by tert-butylhydroperoxide (t-BuOOH). Liver mitochondria were homogeneously isolated from Sprague-Dawley rats (the relative specific activity of succinate dehydrogenase was 35.73 ± 2.78). Addition of 90 µM of t-BuOOH caused a typical 2-phase swelling of the mitochondria. The pattern of swelling was influenced by various factors such as buffer composition, concentrations of t-BuOOH, amount of isolation buffer and mitochondrial proteins and incubation temperature.The swelling could be reduced by as much as 85 ± 3% by 2.50 µM of curcumin. At lower (1.25 µM) or higher (5.00 µM) concentrations, the protection against swelling by curcumin were less effective (respectively were 41 ± 3% and 77 ± 6%). Swelling might occur due to the opening of mitochondrial transition pore and could be an initial indication in the cascade process leading to cell death. The inhibition of t-BuOOH-induced mitochondrial swelling by curcumin might be because of the antioxidant effects of the compound. (Med J Indones 2006; 15:131-6) Keywords: mitochondria, swelling, tert-butylhydroperoxide, curcumin